Estrutura em comunidades de insetos aquáticos: uma abordagem experimental em córregos no município de Niquelândia, Goiás, Brasil - Jesus, Jhonathan Diego Nascimento de (2009)
A broad spectrum of abiotic and biotic factors influences the structure community of aquatic insects. This study was conducted in five intermittent streams in the city of Niquelândia in the State of Goiás, on area of influence of mining company Anglo/CODEMIN, near Serra da Mesa Lake. The material used to construct the artificial substrate was one kilogram of crushed rock (gneiss) surrounded by rings of nylon mesh 0.5 mm, due to the similarity of this material to the natural substrates in sampled streams, formed mostly by stones. Five samples were placed in each stream arranged with the average distance 1 meter between them. The samples were placed in sampling points after the first rain event in the region, since all the streams used in the experiment were dry. Every seven days a sample was withdrawn and replaced by another that remained in streams only seven days. The others remained fourteen, twenty-one, twenty-eight and thirty-five days. The result of quadratic polynomial regression showed a structuring related to the sites sampled and Lake Serra da Mesa, only the second ANCOVA results showed, suggesting a significant community structure analyzed by dominance, although that this arrangement has been low. Thus, was observed that the community addressed were more structured by abiotic factors versus the initial hypothesis that predicted a structure based on patterns of dominance and founder effect, concludes that in early stages of colonization succession the factors that can improve the structure of communities are the abiotic ones.